The effect of hydro-alcoholic extract of Ceratonia Silique L. on spermatogenesis index in rats treated with cyclophosphamide: An experimental study - Firouzeh Sadeghzadeh; Azizeh Sadeghzadeh; Saeed Changizi-Ashtiyani; Sepideh Bakhshi; Farideh Jalali Mashayekhi; Mehry Mashayekhi; Hossein Poorcheraghi; Ali Zarei; Mostafa Jafari (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Ceratonia silique (Ceratonia) is a medicinal herb with antioxidant properties that reduces oxidative stress. Objective: The aim of this study was to investigate the antioxidant effects of Ceratonia extract on improving the toxicity induced by cyclophosphamide (CP) on spermatogenesis. Materials and Methods: 54 male Wistar rats (4 months old) weighing 200-250 gr were randomly divided into 6 groups (n = 9/each): "group 1 (control) underwent the normal diet and water; group 2 (sham) received 2 ml/day normal saline; group 3 (positive control) received 300 mg/kg/day Ceratonia extract; group 4 (Ceratonia + CP) received Ceratonia extract (300 mg/kg/day) + 5 mg/kg/day CP (Endoxan, baxter oncology gmbh, Germany) after 4 hr; group 5 (CP) received 5 mg/kg/day CP + normal saline 4 hr after it; and group 6 (CP + Ceratonia) received Ceratonia extract (300 mg/kg/day) 4 hr after 5 mg/kg/day CP." 24 hr after the last gavage, heart blood sampling was performed to measure the levels of malondialdehyde (MDA), ferric reducing antioxidant power, testosterone, luteinizing hormone, and follicle-stimulating hormone. The left caudal epididymis was cut in the Ham's F10 and the released spermatozoa were used to analyze sperm parameters. The histology of the right testes was studied using stereological techniques and the left testes were used to measure the level of tissue MDA and ferric reducing antioxidant power. Results: A significant increase in the mean level of MDA (p = 0.013) was seen in the CP compared to the control group. Sperm motility (p = 0.001) and count (p = 0.002), serum and tissue total antioxidant (p ≤ 0.001) and serum testosterone levels (p = 0.019) decreased in the CP compared to the control group. Ceratonia extract could significantly prevent the adverse effects of CP on sperm motility (p < 0.001), the mean levels of tissue MDA (p = 0.018), serum total antioxidant (p = 0.045), and testosterone (p < 0.001). Conclusion: The Ceratonia extract can modify the reproductive toxicity of CP in rat due to the presence of antioxidant compounds.